2020
DOI: 10.1007/s00405-020-06391-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 paradoxical vocal fold movement disorder

Abstract: A 28-year-old female presented to the laryngology office with a 7-week history of sudden inspiratory noise and dyspnea. The patients suffered from COVID-19 at the end of March; the diagnosis being confirmed through nasopharyngeal swabs and RT-PCR. The COVID-19 related symptoms lasted 7 days and included loss of taste and smell senses, mild dysphonia, headache, and nasal obstruction. Patient did not have cough or fever. The overall clinical picture was mild to moderate and did not require hospitalization. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 4 publications
0
18
2
1
Order By: Relevance
“…This study hypothesized that respiratory sequelae and vocal tract symptoms related to COVID-19 might be risk factors for the development of dysphonia. This study indicates that hoarseness was present in 48.89% of the cases during the disease, higher rates than those described in the literature regarding dysphonia, which is 27% 12 . In this study, 26.67% of patients presented with symptoms of hoarseness after the disease.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This study hypothesized that respiratory sequelae and vocal tract symptoms related to COVID-19 might be risk factors for the development of dysphonia. This study indicates that hoarseness was present in 48.89% of the cases during the disease, higher rates than those described in the literature regarding dysphonia, which is 27% 12 . In this study, 26.67% of patients presented with symptoms of hoarseness after the disease.…”
Section: Discussioncontrasting
confidence: 55%
“…Dysphonic patients had a higher occurrence of cough, chest pain, sticky sputum, arthralgia, diarrhea, headache, fatigue, nausea, and vomiting. The severity of dyspnea, dysphagia, ear pain, facial pain, sore throat, and nasal obstruction was higher in the dysphonic group than in the non-dysphonic group 12 .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The selection process carried out according to the Preferred Reporting for Systematic Review and Meta‐Analysis (PRISMA) consensus statement is shown in Figure 1. The published cases are summarized in Table 1 35–56 . Twenty‐two articles were finally selected for the qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that dysphonia persisted at least 1-month post-hospitalization. The study of dysphonia in COVID-19 patients is important regarding the neurotropism of the virus and the expression of angiotensin converting enzyme 2 (ACE2) in vocal folds [2] , [3] . We congratulate authors for this research.…”
mentioning
confidence: 99%